Living on the Edge: Contrasted Wood-Formation Dynamics in Fagus sylvatica and Pinus sylvestris under Mediterranean Conditions - Martinez del Castillo, Edurne; Longares, Luis A.; Gričar, Jožica; Prislan, Peter; Gil-Pelegrín, Eustaquio; Čufar, Katarina; de Luis, Martin (Frontiers in Plant Science, 2016)
Wood formation in European beech (Fagus sylvatica L.) and Scots pine (Pinus sylvestris L.) was intra-annually monitored to examine plastic responses of the xylem phenology according to altitude in one of the southernmost areas of their distribution range, i.e. in the Moncayo Natural Park, Spain. The monitoring was done from 2011 to 2013 at 1180 and 1580 m a.s.l., corresponding to the lower and upper limits of European beech forest in this region. Microcores containing phloem, cambium and xylem were collected biweekly from twenty-four trees from the beginning of March to the end of November to assess the different phases of wood formation. The samples were prepared for light microscopy to observe the following phenological phases: onset and end of cell production, onset and end of secondary wall formation in xylem cells and onset of cell maturation. The temporal dynamics of wood formation widely differed among years, altitudes and tree species. For Fagus sylvatica, the onset of cambial activity varied between the first week of May and the third week of June. Cambial activity then slowed down and stopped in summer, resulting in a length of growing season of 48–75 days. In contrast, the growing season for Pinus sylvestris started earlier and cambium remained active in autumn, leading to a period of activity varying from 139-170 days. The intra-annual wood-formation pattern is site and species-specific. Comparison with other studies shows a clear latitudinal trend in the duration of wood formation, positive for Fagus sylvatica and negative for Pinus sylvestris.